Assessment of performance degradation of hybrid flax-glass fiber reinforced epoxy composites during a salt spray fog/dry aging cycle. (1st June 2022) - Fiore, V.; Calabrese, L.; Miranda, R.; Badagliacco, D.; Sanfilippo, C.; Palamara, D.; Valenza, A.; Proverbio, E.
Abstract: The main goal of this paper is the evaluation of the performances reversibility of hybrid composites when they are dried after being aged in salt-fog environment. To this aim, epoxy composites reinforced with flax and glass fabrics respectively in the internal and external laminae were at first exposed to salt-fog (i.e., identified as wet phase) and then stored in controlled conditions (i.e., identified as dry phase). The flexural properties evolution of these composites as well as their water uptake and contact angle were monitored at varying time of both phases. The flexural strength and modulus of hybrid composites is 23.4% (17.9%) and 15.5% (12.9%) lower than unaged ones after 30 (15) days of salt-fog exposition, respectively. However, the dry phase allows an almost complete recovery of the composite performances. In particular, samples exposed to salt-fog for 30 days show an adequate recovery in the stiffness at the end of the dry phase, whereas their strength is about 10% lower than unaged ones. Highlights: Flax-glass hybrid composites were aged under alternated salt-fog and dry steps. Flexural tests, water uptake and water contact angle measurements were performed. Hybrid composites experienced reversible and irreversible degradative phenomena. Due to the dry phase, hybrid composites showed an adequate recovery in flexural stiffness. A topological map discriminating reversible and irreversible aging zones was proposed.